Contribuições ao estudo da secagem da borra de café em leito vibrofuidizado - Rocha, Thalyne de Almeida Ferreira (Universidade Federal de São Carlos, 2019)
Brazil is the largest producer of coffee in the world, half of this production is destined to the soluble coffee industry, that generates a amount of waste. The spent coffee grounds leave the fabrication processo f the soluble coffee with 70% (w.b.) moisture content, the reduction of moisture present is essential to reduce storage and transport costs, as well as increase the heating value for direct burning. This work presents characterized the dry and wet spent coffee grounds, through particle size analysis, aparent and bulk density, Hausner index and bed porosity. The analysis of the fluid dynamics of coffee grounds as a function of moisture contente was done, with the purpose of delineating the behavior of the fluidized bed material, identifying the change in fluidization behavior between 40 and 60% moisture contente (w.b.). It analyzed the dry bed elutriation by classifying the particles depending on the speed of the air. Subsequently a mechanical dewatering study was carried out, obtaining a moisture reduction of 0.70 to 0.45 (w.b.) of the spent coffee grounds, obtaining that the pressure applied and the pressing time exerts a statistically significant influence in this step. Finally, the study of thermal drying with experimental design 2² and replica at the central point in a vibrated fluid bed dryer using three different vibrational configurations (vibrofluidized with Γ=4 formed by A=0.015m and f=8.14Hz; vibrofluidized , Γ=4 for A=0.003m and f=18.20Hz and fluidized bed, Γ=0) using the air velocity between 4 and 6 Umf and temperature between 50 and 70ºC. Through the individual planning of each configuration one can verify statistically the main responses of the system: feed rate, elutriate production, moisture content and particle diameter. For the low air velocities, high feed rates and increased elutriate production were obtained, favored mainly by the vibration amplitude of 0.003mm. In all tests, moisture was obtained below 30%, where the industrial boiler has already been burned efficiently. When evaluating the diameter of the powder for flow and burning, the best conditions were found at high speeds and temperatures and greater amplitude of vibration.
Contributions to the study of the drying of spent coffee grounds in vibrofuidized beds
Keywords: Borra de café; Secagem; Fluidização; Leito fluidizado; Leito vibrofluidizado; Fluidodinâmica; Spent coffee grounds; Drying; Fluidization; Fluidized bed; Vibrofluidized bed; Fluid dynamics; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA